FAKTOR YANG MEMPENGARUHI MINAT PESERTA DIDIK DALAM MEMANFAATKAN KONSELING INDIVIDUAL - Aditia Teguh Amora; Rahma Wira Nita; Citra Imelda Usman (STKIP Pesisir Selatan, 2025)
This research is motivated by the existence of several students who experience obstacles in their interest in participating in individual counseling. In addition, students do not understand the impact caused if obstacles to interest in participating in individual counseling are allowed, so that the learning process in the classroom does not run effectively and students become less focused because they harbor the problems they have. The purpose of this study is to find out the factors that affect students' interest in participating in individual counseling services, both from internal and external factors. This study uses a quantitative descriptive method. The research population was 323 students in class VIII, with purposive sampling techniques of 50 people, namely students who had participated in individual counseling. The instrument used was in the form of a questionnaire, and data analysis was carried out using percentages. The results showed that 1) internal factors that affect students' interest are in the category of quite high, and 2) external factors that affect students' interest in utilizing individual counseling are in the category of quite high (78%). This study recommends that BK teachers can increase students' interest in utilizing individual counseling services.